INCLUSIVE EDUCATION PROGRAM IN MALAYSIA: EVOLUATION IN POLICY AND CHALLENGES (Proceedings of International Conference on Special Education, 2015)
Inclusive education was strengthened through the Malaysia Education Blueprint 20132025. However, there are some issues encountered in its implementation in schools. Questions of how the development of Inclusive Education Programme in Malaysia and what are the issues faced in implementing the Inclusive Education Programme in schools have been raised. Therefore, the objective of this study is to identify the development of inclusive education and issues encountered in its implementation in Malaysia. This research was the analysis of documents and information obtained and compiled based on six categories: pre-independence, post-independence, education development during the era of new economic policy, education development during the era of national development policy, education development during the era of national vision policy and education development through the national key result areas (NKRA). The study also examines at the evolution of inclusive education starting from preindependence to date, and is limited in Malaysia only. The study found that the evolution of inclusive education in Malaysia as an international education and support requirements of the Education for All (EFA) and receives special attention from the government through Malaysia Education Blueprint 2013-2025. There are three issues in the implementation of inclusive education, which are inconsistencies in the implementation of Inclusive Education Programme, collaborative parties involved in the school and the adaptation